Identifikasi Telur Cacing pada Sayur Lalapan yang Dijual Pedagang Warung Tenda Pinggir Jalan di Distrik Abepura Kota Jayapura - Nike Sulastri; Apriani Herni Rophi; Ruth Megawati (Konstanta : Jurnal Matematika dan Ilmu Pengetahuan Alam, 2024)
Worms are an infectious disease caused by parasites in the form of worms. According to data from the Papua Province Health Service in 2011, the number of worm cases was 528.8 per 1,000 population, while in the Jayapura City Health Service the number of worm cases in 2011 was 2.48 per 1,000 population. According to data from the Abe Pantai Community Health Center, the prevalence of worms in 2012 was 3.21 per 1,000 population. The prevalence in Hedam Community Health Center, Waena Community Health Center and Kotaraja Community Health Center in 2012 was 1.94 per 1,000 population, 1.25 per 1,000 population, 0.94 per 1,000 population, respectively. Vegetables that are eaten directly are at risk of being contaminated by various types of parasites during planting, harvesting and marketing and have the potential for transmission of infection to humans. This study aims to determine whether or not there is contamination with STH (Soil transmitted helminth) worm eggs contained in fresh vegetables from roadside tent stalls in Abepura District. The type of research used is descriptive research using a laboratory approach. The research sample was 20 samples of roadside tent stall traders in Abepura District taken using Random Sampling Technique. The method for examining worm eggs uses the Sedimentation method. The results of identification of worm eggs in fresh vegetables sold by roadside stall vendors in Abepura District showed that there was worm egg contamination found in 20 samples of fresh vegetables, with 8 samples contaminated or 40% and 12 samples or 60% not contaminated with worm eggs Soil transmitted helminth. The types of Soil Transmitted Helminth worm egg species found were Ascaris lumbricoides (35%), Trichuris trichiura (30%) and Hookworm (30%)